The role of the accountant in preventing money laundering - Cvetković Dragan; Vujičić Slađana; Stanković Sunčica (Trendovi u Poslovanju)
Legalization of illegally obtained income, money laundering is an extremely negative social phenomenon, represented both on a national and international scale. The inclusion of illegally acquired income in legal financial flows not only undermines the economic and monetary system, but also undermines the political stability and security of the state. The concern about money laundering has become one of the main preoccupations of governments and financial sector regulatory bodies around the world. One of the state's responses to this negative phenomenon is an effective system for combating money laundering and terrorist financing. A system characterized by partnership between the private and public sectors, coordination and cooperation between competent state authorities and all its participants/obligors. The accounting profession plays an important role in the financial system by facilitating transactions that support the nation's economy. Accountants are obliged to apply and observe the measures and actions prescribed by law related to the prevention of money laundering, thereby ensuring that their services are not used for criminal purposes. The aim of this paper is to expand the spectrum of knowledge about the phenomenon of money laundering and to point out the significant role of accountants in a complex and dynamic process such as the prevention of money laundering.